Vaginal biopsy, pregnancy detection and induction of farrowing in crossbred sows - NEAUPANE, T R; PANDIT, R K; JOGI, S; SHRIVASTAVA, O P; AGARWAL, R G (The Indian Journal of Animal Reproduction, 2003)
Thirty six 3/4 Large White Yorkshire X ¼ Indigenous sows were used to delineate (1) vaginalcellular picture during different phases of reproduction and (2) effect of induction of farrowing. Infirst part, 18 sows according to reproductive status were placed equal number in 1. Pregnant, 2.Nonpregnant and 3. Estrus groups. There was thin vaginal epithelial layer during 28 - 31 days ofpregnancy. During diestrum i.e. 14 days after end of estrum the vaginal epithelial lining was also thinbut comparatively more than during pregnancy. The vaginal epithelial cells during estrum depictedgreatly thickened epithelium with clear interpapillary pegs. The pregnancy diagnosis through vaginalbiopsy between 28 to 31 days of service was 100% accurate. In second part, 18 pregnant animals wererandomly placed in equal number to Group 4 (2 ml 0.392 mg tiaprost trometamol, 20 -30 hours beforefarrowing intramuscularly), 5 (half dose of the drug than in former group intravulvosubmucosally)and 6 (control). The duration of onset of farrowing was significantly earlier (P< 0.01) in Group 4 (23.41± 1.11 h) than Group 5 (43.14 ± 1.62 h). Time taken for completion of farrowing/ occurrence ofstillbirths ( 3.58 ± 0.67 h vs 3.5 ± 0.32 h/0.33 ± 0.21 vs 0.50 ± 0.22) did not differ significantly betweenboth the groups. However, the number of stillbirths were significantly more (P < 0.01) in the controlgroup (2.17±0.30).
Keywords: Pregnancy diagnosis; Farrowing induction; Vaginal biopsy; Sows